E-072 Post-coital MCA Dissection Presenting with SAH: A Case Report and Review of the Literature. (26th July 2014) - Alawi, A; Mehta, S; Edgell, R
Abstract : Background: Post-coital dissections are uncommon and have been reported rarely in the aorta and coronary arteries. Intracranial arterial dissections are rare and data regarding this disease process is scant. We present a case of post-coital middle cerebral artery (MCA) dissection in a young man presenting with subarachnoid haemorrhage (SAH). Methods: Case report and review of the literature. Case report: A 35-year-old man with no past medical history presented with severe headache that started immediately after sexual intercourse. This was also associated with transient left facial weakness which resolved after a few minutes. His headache subsided initially but recurred spontaneously three days later prompting a visit to the ER. He denied any history of trauma. His neurologic exam was unremarkable. A head CT showed SAH in the right Sylvian fissure and sulci of the superior right frontal lobe. He underwent a catheter angiogram which revealed an area of focal narrowing in the right MCA M1 segment caused by a dissection flap and slow flow distal to the area of the luminal stenosis (Figure 1a ). MRI of the brain showed small punctate right hemispheric infarcts. Anticoagulation with warfarin was initiated and patient was discharged home. The patient remained clinically stable and underwent a follow up angiogram after 4 months, which showed interval change in the right MCA dissection with development of severe stenosis in the proximal M1 segment (Figure 1b ). There was slow antegrade flow distal to the stenotic segment and collateral flow through pial collaterals from the right ACA to the distal right MCA branches. Discussion: Intracranial arterial dissections are uncommon and may present with severe headache. These may cause cerebral infarctions or subarachnoid haemorrhage. Most reported intracranial arterial dissections affect the vertebrobasilar circulation. In addition, nontraumatic spontaneous dissection of the MCA is rare. Rupture of the dissected arterial wall, either directly or at the site of an aneurysm, can cause subarachnoid haemorrhage. The natural history of this disease process is not very well understood. There may be resolution of the stenosis, formation of pseudoaneurysms, or, as seen in our case, worsening of the severity of stenosis. Our patient had no subsequent clinical events as he had good collateral circulation. Our case highlights this rare cause of non-aneurysmal SAH and we believe this to be the first reported case of post-coital MCA dissection. Disclosures: A. Alawi: None. S. Mehta: None. R. Edgell: None.